Formation of light impurities in a hydrogen plasma at initial stage of a discharge - Yuferov, V.B.; Skibenko, E.I.; Tkachov, V.I.; Katrechko, V.V.; Svichkar, A.S. (Вопросы атомной науки и техники, 2019)
Analyzing the dynamics of density for atomic and molecular hydrogen ions, the values of atomic hydrogen and UV radiation fluxes to the walls of the plasma chamber were obtained, resulting in light impurities of carbon and oxygen at plasma start-up during the process of desorption from the walls under irradiation. The fluxes of impurity atoms associated with the fluxes of photons and hydrogen atoms in a discharge are determined. Recommendations are given to reduce the amount of impurities at the initial stage of discharge.